ANALISIS PERMINTAAN KREDIT INVESTASI PADA BANK SWASTA NASIONAL DI JAWA TIMUR - Daryanti Ningsih; Idah Zuhroh (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2010)
This research aims to know influence of mount rate of interest of investment credit and inflation to investment credit of demand in national state bank east java. In this research use sekunder data which have been publicated by Bank of Indonesia and use double linier regretion and using eviews program. The solution focused at growth of investment credit of demand in national state bank at east java. From the result analyse obtained that both of the variable used in this model, channelization investment credit still very base on level of rate of credit and inflation. For a while from test conducted by hypothesizing test obtained rate credit have effect significant to investment credit of demand in national state bank east java, inflation no have effect significant to investment credit of demand in national state bank at east java